Enhanced strain and stiffness evaluation of virgin and recycled single carbon fibres by means of one-dimensional digital image correlation. (7th February 2019) - Huether, Jonas; Esse, Daniel; Rupp, Peter; Seitz, Michael; André Weidenmann, Kay
Abstract: The Young's modulus of single carbon fibres, virgin and recycled, is investigated in this study. Single fibre measurements are enhanced in two fields: firstly, the cross-sectional area is calculated by taking individual measurements with a laser diffraction sensor and applying a sinusoidal fit to account for irregular fibre shapes. Secondly, strains during the loading cycle are measured directly by applying fluorescing tracking markers on the fibre and using one-dimensional digital image correlation. Several markers are applied on each side of the fibre to allow for a statistically verified evaluation. To achieve high-resolution images, a step-wise load cycle is applied. The load is increased in steps of until final failure. It is demonstrated that direct strain measurement and enhanced determination of the Young's modulus are possible for carbon fibres. It was further shown that the recycling of the carbon fibre by pyrolysis reduced the Young's modulus by approximately 10% compared to virgin fibres.